Association Between Preoperative Monocyte to High-Density Lipoprotein Ratio on In-hospital and Long-Term Mortality in Patients Undergoing Endovascular Repair for Acute Type B Aortic Dissection - Xie, Enmin; Yang, Fan; Luo, Songyuan; Liu, Yuan; Xue, Ling; Huang, Wenhui; Xie, Nianjin; Chen, Lyufan; Liu, Jitao; Yang, Xinyue; Su, Sheng; Li, Jie; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims: The monocyte to high-density lipoprotein ratio (MHR), a novel marker of inflammation and cardiovascular events, has recently been found to facilitate the diagnosis of acute aortic dissection. This study aimed to assess the association of preoperative MHR with in-hospital and long-term mortality after thoracic endovascular aortic repair (TEVAR) for acute type B aortic dissection (TBAD). Methods: We retrospectively evaluated 637 patients with acute TBAD who underwent TEVAR from a prospectively maintained database. Multivariable logistic and cox regression analyses were conducted to assess the relationship between preoperative MHR and in-hospital as well as long-term mortality. For clinical use, MHR was modeled as a continuous variable and a categorical variable with the optimal cutoff evaluated by receiver operator characteristic curve for long-term mortality. Propensity score matching was used to diminish baseline differences and subgroups analyses were conducted to assess the robustness of the results. Results: Twenty-one (3.3%) patients died during hospitalization and 52 deaths (8.4%) were documented after a median follow-up of 48.1 months. The optimal cutoff value was 1.13 selected according to the receiver operator characteristic curve (sensitivity 78.8%; specificity 58.9%). Multivariate analyses showed that MHR was independently associated with either in-hospital death (odds ratio [OR] 2.11, 95% confidence interval [CI] 1.16-3.85, P=0.015) or long-term mortality (hazard ratio [HR] 1.78, 95% CI 1.31-2.41, P<0.001). As a categorical variable, MHR>1.13 remained an independent predictor of in-hospital death (OR 4.53, 95% CI 1.44-14.30, P=0.010) and long-term mortality (HR 4.16, 95% CI 2.13-8.10, P<0.001). Propensity score analyses demonstrated similar results for both in-hospital death and long-term mortality. The association was further confirmed by subgroup analyses. Conclusions: MHR might be useful for identifying patients at high risk of in-hospital and long-term mortality, which could be integrated into risk stratification strategies for acute TBAD patients undergoing TEVAR.